Lingual disposition of Sakha in education in context of modern extralinguistic realities (based on polls in Yakutsk) - Ivanova, Nina I. (The New Research of Tuva, 2018)
Article presents the results of sociolinguistic survey conducted by the author in 2007-2008, 2014 and 2016 – an opinion poll of residents and experts of Yakutsk representing Sakha (Yakut) population regarding the language preferences in the field of pre-school and school education. Hence the author taps the level of vitality of Sakha language and lingual loyalty of its contemporary bearers.In 2008 most of respondents were supporters of strategy of early pre-school Russian language education and teaching of Yakut language on vernacular level. In 2014 preferences have shifted towards mixed teaching in kindergarten with strong disposition for ethnic environment. An increase of lingual loyalty of a city population have been detected with aspiration to create conditions for ethnocultural evolution. Nonetheless, reality in city of Yakutsk doesn’t allow education on Yakut language from grade 1 to 11 and is remaining an eligible condition in the answers or respondents.Priorities of the state language policies of Russia and the Republic of Sakha (Yakutia) in education are being analyzed in the article. It is noted, that the Law “On languages in the Republic of Sakha (Yakutia)” guarantees free choice of language for education. It is republican authorities’ liability to insure the constitutional right for education in mother tongue. Reality reveals leak of administrative and legal base, curricular support and professional qualification of teachers of Yakut language.
Keywords: Yakutia; Yakut language; Yakuts; sociolingual aspect; Sakha language; bilingualism; problems of education; public opinion